Brief problem-solving therapy for antenatal depressive symptoms in primary care in rural Ethiopia: protocol for a randomised, controlled feasibility trial - Bitew, T.; Keynejad, R.; Myers-Franchi, Bronwyn; Honikman, S.; Medhin, G.; Girma, F.; Howard, L.; Sorsdahl, K.; Hanlon, C. (2021)
Background: Despite a high prevalence of antenatal depression in low- and middle-income countries, there is very little evidence for contextually adapted psychological interventions delivered in rural African settings. The aims of this study are (1) to examine the feasibility of procedures for a future fully powered efficacy trial of contextually adapted brief problem solving therapy (PST) for antenatal depression in rural Ethiopia, and (2) to investigate the acceptability, fidelity and feasibility of delivery of PST in routine antenatal care.